2017
DOI: 10.1089/pop.2016.0051
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Frequent Emergency Department Use by Pediatric Medicaid Patients

Abstract: The objective of this study was to determine the patient characteristics and health care utilization patterns that predict frequent emergency department (ED) use (≥4 visits per year) over time to assist health care organizations in targeting patients for care management. This was a retrospective, population-based study of 13,265 Medicaid children aged 0-20 years who were attributed to a single pediatric accountable care organization for at least 2 consecutive years between June 2012 and May 2015. Year-to-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 31 publications
3
21
0
Order By: Relevance
“…In agreement with previous analyses using 2000 to 2002 MEPS data, children with public insurance were more likely to have two or more ED visits and high EDR than children with private insurance . Contrary to findings from studies conducted in large, free‐standing children's hospitals, only 2.1% of children in the MEPS sample who visited the ED in the past year had four or more ED visits . Our findings indicate that publicly insured children are more likely to have visited the ED in the study year and to be reliant on the ED for health care.…”
Section: Discussionsupporting
confidence: 87%
“…In agreement with previous analyses using 2000 to 2002 MEPS data, children with public insurance were more likely to have two or more ED visits and high EDR than children with private insurance . Contrary to findings from studies conducted in large, free‐standing children's hospitals, only 2.1% of children in the MEPS sample who visited the ED in the past year had four or more ED visits . Our findings indicate that publicly insured children are more likely to have visited the ED in the study year and to be reliant on the ED for health care.…”
Section: Discussionsupporting
confidence: 87%
“…Children with high ED use were defined as having 4 or more ED visits in 2012 (a threshold we selected on the basis of use in multiple previous studies). 1,2,4 We then measured the number of ED visits each child experienced in 2013 and 2014. We characterized the reasons for each ED visit using the diagnosis grouping system, a classification system developed specifically for categorizing the reasons for pediatric ED visits on the basis of International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) billing codes.…”
Section: Measuring Ed Visitsmentioning
confidence: 99%
“…1 -5 In previous studies, researchers have demonstrated that children with 4 or more ED visits in a single year account for between 13% and 42% of all ED use at pediatric EDs. 1,2,4 Medicaid-insured children often visit the ED at higher rates than privately insured children. 1, 6 -9 The reasons cited for higher ED use among Medicaid enrollees include higher burdens of certain chronic conditions and worse access to timely primary 10 and preventative care.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have identified patient characteristics that are associated with frequent pediatric ED visits including chronic disease, minority race, social determinants, age (particularly younger than 1 year), and public insurance. 1214 Potential etiologies have included limited clinic office hours, increased clinic wait times, and lack of an identified usual source of care. 15 Parents with low health literacy were inclined to overestimate severity of illness and seek care sooner and visit a clinic only when an appointment is available within hours.…”
mentioning
confidence: 99%